GIS application for solution of the problems of public transportation system in Zilina - Sitanyiova, Dana; Masarovicova, Sona (Communications - Scientific letters of the University of Zilina, 2004)
The paper deals with the public transportation system in Zilina. The research study initiated by the Transportation Company of Zilina has been performed with the aim to solve the problems concerning public transportation service in the urban area. The main goal of the research study was to evaluate how well the bus stops serve the public and to identify the segments of the traffic routes, which are risky for buses and trolleybuses operation. Geographic information system was applied to solve these problems by analysing the geospatial data referring to the transportation system. The paper includes the outputs from these analyses.